UNIVERSIDADES POPULARES: LA BÚSQUEDA DE LA GENEALOGÍA PROPIA (De Signos y Sentidos, 2018)
Traditionally, historiography has considered the expansion of the Popular Universities (PU) throughout Latin America as a product of the reformist ideal and its spreading throughout the continent. Some of those approximations to the subject were focused on the experiences in Perú, specifically, the González Prada Popular Universities. These PU were considered as the paradigmatic case of the connection between University Reform and the expansion of this type of educational proposal related to the reformist university. In this paper we will try to trace the experiences of the PU, in Latin America and in Europe, before the breakout of the University Reform in Córdoba (1918) and to question that relationship which, it is our contention, has not been properly studied in depth.
Keywords: University Reform; popular universities; popular education